PERBEDAAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIII YANG MEMPEROLEH PEMBELAJARAN DENGAN METODE PROBLEM BASED LEARNING DAN PROBLEM SOLVING DI SMP NEGERI 2 METRO - Suryatul Aini Asyhara; Desrina Hardianti (Universitas Muhammadiyah Lampung, 2018)
The purpose of this study is to determine whether there are differences in the average learning outcomes of mathematics and which are higher average learning outcomes of mathematics between students who use the learning methods Problem Based Learning and Problem Solving. This type of research is experimental. Data analysis techniques using the ttes formula. The results showed that: (1) there were differences in the average learning outcomes of mathematics between students who used the Problem Based Learning and Problem Solving learning methods at SMPN 2 Metro, this was known based on the calculation of the hypothesis test obtained thit = 2,60 and tdaf = 2,00 so thit> tdaf. (2) the average student learning outcomes using the Problem Based Learning method are higher than the Problem Solving learning method in mathematics learning for VIII grade students of SMP Negeri 2 Metro 2016/2017 Academic Year, this is known based on the two average test difference, obtained thit = 2,53 and tdaf. = 1,67 so thit > tda